PENGARUH DIABETES SELF MANAGEMENT EDUCATION (DSME) TERHADAP TINGKAT KECEMASAN, KUALITAS TIDUR DAN KADAR GULA DARAH PENDERITA DIABETES MELITUS TIPE 2 - Seni Nilam Sari (2023)
Diabetes Mellitus is a chronic disease that has an increasing number of incidents and deaths every year that require serious treatment by involving sufferers in self-care management through the Diabetes Self Management Education (DSME) approach. DSME is a process to facilitate knowledge, skills and self-management abilities to control symptoms and avoid complications. The aim of the study was to determine the effect of Diabetes Self Management Education (DSME) on anxiety levels, sleep quality and blood sugar levels of type 2 diabetes mellitus in the work area of the Kelapa Gading Health Center. The pre-experimental research method was a one group pre-post test design with a consecutive sampling technique of 40 respondents. The research was conducted in 2 sessions through calendar media in 3 weeks. Hamilton Anxiety Rating Scale (HARS) questionnaire measures anxiety level, Pittsburgh Sleep Quality Index (PSQI) sleep quality & glucometer, blood sugar observation sheet. The results of the study, the Wilcoxon Signed Rank Test test for anxiety levels, sleep quality and blood sugar levels before and after the intervention (p-value = 0.000 <0.05), means that there is a significant effect of Diabetes Self Management Education (DSME) on anxiety levels, sleep quality and blood sugar levels in type 2 diabetes mellitus. This research is expected to carry out self-management & DSME as a program that continues to be implemented and developed in nursing practice in health centers, hospitals and other health institutions.